The Wear Pattern of Router Cutter Material Between High Speed Steel and Solid Tungsten Carbide in Cutting Rubberwood Medium Density Fiberboard - Bakeri, Ahmad Bahtiar (2002)
In order to study the wear pattern of router cutter material between High speed steel and Solid tungsten carbide in cutting rubberwood MDF two type of router cutter material (HSS and STC) were employed. The solid tungsten carbide showed the longest working life (twice the cutting distance compare to high speed steel), while the high speed steel retained its usefulness for only a short distance of cutting (tool life). It was confirmed that the steel wore faster than tungsten. The observation show that solid tungsten carbide is more suitable because it wear only a few micron compared to high speed steel in cutting rubberwood MDF but high speed steel can be sharpened to improve it's performance but at an extra cost and time. It is more economic and productive. Solid tungsten carbide is the better alternative as there are many constrained.